A Laodicean : a story of today - Hardy, Thomas (London : Everyman, 2010)
In "A Laodicean" (1881) Mr. Hardy became less spontaneous and charming, although more subtle and, perhaps, more powerful. The heroine, Paula Power, the Laodicean, neither hot nor cold, is a most interesting study in feminine psychology. The three leading male characters$1 (BSomerset, the architect, Dare, the adventurer, and Captain de Stancy, the scion of a decayed family$1 (Bare well drawn.s
Keywords: Castles -- Fiction. -- Conservation and restoration